International Human Rights Instruments and Indonesian Legal Protection For Persons With Disabilities - Elfia Farida1 , Adya Paramita Prabandari1 , Rahayu1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Persons with disabilities as Indonesian citizens, in fact have the same position, rights and obligations asother Indonesian citizens. This is guaranteed in the Indonesian Constitution. This study aims to discuss abouthow the legal protection for persons with disabilities in Indonesia. The juridical normative research methoduses a statute approach and conceptual approach, and then the data is processed and analyzed qualitatively.Legal protection for persons with disabilities is the responsibility of the state. Indonesia has ratified theConvention on the Rights of Persons with Disabilities, which was followed up with the revocation of Lawno. 4 of 1997 concerning Disabled Persons, then enactment of Law No. 8 of 2016 concerning Personswith Disabilities, which prioritizes the issue of human rights. Persons with disabilities are seen as subjectswhose rights must be protected for the sake of their dignity. For the enforcement mechanism, the NationalDisability Commission was formed based on Presidential Regulation No. 68 of 2020, but the substance isnot in accordance with the human rights and independent principles because it is attached to the Ministry ofSocial Affairs which should be the object of its supervision. Therefore the President must immediately reviseit in accordance with the mandate of Law No. 8 of 2016.